11β-hydroxysteroid dehydrogenase type 1 and pregnancy: Role in the timing of labour onset and in myometrial contraction. (15th May 2017) - Damiani, Francesco; Makieva, Sofia; Rinaldi, Sara F.; Hua, Lei; Marcolongo, Paola; Petraglia, Felice; Norman, Jane E.
Abstract: Glucocorticoids play a primary role in the maturation of fetal organs and may contribute to the onset of labour. Glucocorticoid activity depends on the 11β-hydroxysteroid dehydrogenase family (11β-HSDs), catalysing the interconversion between "active" cortisol into inactive cortisone. No definitive study exists on 11β-HSD expression profile in human decidua and myometrium during pregnancy. We investigated the implications of 11β-HSD1 in the regulation of uterine activity in pregnancy, examining its role on contraction of a myocyte cell line and murine 11β-hsd1 levels in utero. Murine 11β-hsd1 mRNA and protein levels in utero progressively increased until the last day of gestation and significantly decreased at the onset of labour (P < 0.0001) ( n  = 3 to 5 in the various gestational days analysed). Experiments on human myometrial samples confirm the significant fall in 11β-hsd1 mRNA levels at labour, compared to end pregnancy samples ( n  = 5 to 8). In vitro experiments showed that human myometrial contraction is inhibited by using a non-selective inhibitor of 11β-HSD1. The present study shows the temporal localisation of 11β-HSD1 in uterus, highlighting its importance in the timing of gestation and suggesting its contribution in the myometrium contraction. Highlights: The expression profile of 11β-HSD1 in murine uterus during pregnancy was examined. 11β-HSD1 increases in the mouse uterus from early to term-pregnancy. Murine 11β-HSD1 in uterus significantly decreased at the onset of labour. 11β-HSD1 is lower at the onset of labour compared to term in the human myometrium. Human myometrial contraction was inhibited in vitro by using carbenoxolone.